Carbene-catalyzed intermolecular dehydrogenative coupling of aldehydes with C(sp³)−H bonds - Su, Fen (2023)
The development of catalyst-controlled methods for direct functionalization of two distinct C-H bonds represents an appealing approach for C-C formations in synthetic chemistry. Herein, we describe an organocatalytic approach for straightforward acylation of C(sp3 )-H bonds employing readily available aldehyde as "acyl source" involving dehydrogenative coupling of aldehydes with ether, amine, or benzylic C(sp3 )-H bonds. The developed method affords a broad range of ketones under mild conditions. Mechanistically, simple ortho-cyanoiodobenzene is essential in the oxidative radical N-heterocyclic carbene catalysis to give a ketyl radical and C(sp3 ) radical through a rarely explored intermolecular hydrogen atom transfer pathway, rendering the acylative C-C formations in high efficiency under a metal- and light-free catalytic conditions. Moreover, the prepared products show promising anti-bacterial activities that shall encourage further investigations on novel agrochemical development.